Digital Forensic Advanced Evidence Collection and Analysis of Web Browser Activity - Majeti, Ganesh; YVL, Sai Sundar; Ulichi, Sai Shanmukh; Mohanty, Sachi Nandan; S. V., Sudha (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Web browsers are the applications that the majority of computer users utilize the most. Users carry out a wide range of tasks, including accessing the internet, downloading files, and using social media programs, using a web browser to access email accounts. Many crimes committed using digital resources need to be investigated by looking at online browser history. Such information must be included in the reports of the examiners that will generate one of the data gathered, particularly about crimes involving entering the URL, downloaded files, access times, search phrases browser type, and times. Different methods are used by web browsers to store user data. Additionally, the locations where data is stored vary depending on the operating system being used. The analysis of web browsers on digital resources that are subject to criminal activity, data from various browsers on various operating systems, storage types, and data types that can be retrieved are all demonstrated in this study. Also, we demonstrated the capabilities and tools used in the web browser to review the records.